2013
DOI: 10.1071/py11130
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of multicultural health workers in chronic disease prevention and self-management in culturally and linguistically diverse populations: a systematic literature review

Abstract: With a large and increasing culturally and linguistically diverse (CALD) population, the Australian health care system faces challenges in the provision of accessible culturally competent health care. Communities at higher risk of chronic disease include CALD communities. Overseas, multicultural health workers (MHWs) have been increasingly integrated in the delivery of culturally relevant primary health care to CALD communities. The objective of this systematic review was to examine the effectiveness of MHW in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Table 1 summarizes the eight systematic reviews that met the inclusion criteria for this review (Goris et al, 2013; Hawthorne et al, 2010; Heo & Braun, 2014; Huang & Garcia, 2018; Joo, 2014; McCurley et al, 2017; Renzaho et al, 2010; Zeh et al, 2012). The reviews were conducted in Australia ( n = 2), the United Kingdom ( n = 2), and the United States ( n = 4) and were published between 2010 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the eight systematic reviews that met the inclusion criteria for this review (Goris et al, 2013; Hawthorne et al, 2010; Heo & Braun, 2014; Huang & Garcia, 2018; Joo, 2014; McCurley et al, 2017; Renzaho et al, 2010; Zeh et al, 2012). The reviews were conducted in Australia ( n = 2), the United Kingdom ( n = 2), and the United States ( n = 4) and were published between 2010 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Although the focus was initially on cervical cancer, the recommendation was to broaden the remit to include breast and bowel cancers. Evidence has shown that Multicultural Health Workers (MHWs) are critical to the success of cancer screening programs targeting CALD communities, 16 accordingly, it was decided that this program needed to be delivered by trained MHWs in culturally sensitive and safe community settings.…”
mentioning
confidence: 99%
“…It incorporated tailored resources developed in partnership with communities around identified topics (healthy eating, physical activity, chronic disease prevention and self‐management, alcohol consumption and smoking cessation). The program was delivered by trained Multicultural Health Workers from each community and utilises a self‐management framework and adult learning principles to facilitate behaviour change, and promote health and well‐being (Goris, Komaric, Guandalini, Francis, & Hawes, ). The LWM‐LMP is an eight‐week program with two follow‐up sessions.…”
Section: Methodsmentioning
confidence: 99%